2021
DOI: 10.2147/jep.s308388
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of an Intravitreal Humanized Anti-VEGF-A Monoclonal Antibody (PRO-169), a Biosimilar Candidate to Bevacizumab

Abstract: Background PRO-169 is a biosimilar candidate to bevacizumab (BEV), a monoclonal antibody (mAb) that inhibits vascular endothelial growth factor-A (VEGF-A) developed for intravitreal use. The current study demonstrates the intraocular pharmacokinetics (PK) of PRO-169 and its safety using New Zealand white (NZW) rabbits. Methods Intraocular concentration was evaluated in thirty-six rabbits at 1h, 1, 2, 5, 14 and 30 days after a single bilateral injection of PRO-169 or BEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Di Antonio et al [48] performed IVA treatment on 15 eyes of mCNV patients and finally found that the patients not only showed improved BCVA but also reduced central retinal thickness significantly, as well as having decreased levels of VEGF and placental growth factor (PIGF). In addition, bevacizumab is a humanized monoclonal antibody (IgG1) targeting VEGF-A to inhibit angiogenesis, and is composed mainly of an Fab region that binds to the target and an Fc region that performs an effector function [49] . Fothurmore, ranibizumab is also a humanized monoclonal antibody fragment, but it only contains an Fab fragment, which can also inhibit VEGF-A and prevent the formation of new blood vessels [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Di Antonio et al [48] performed IVA treatment on 15 eyes of mCNV patients and finally found that the patients not only showed improved BCVA but also reduced central retinal thickness significantly, as well as having decreased levels of VEGF and placental growth factor (PIGF). In addition, bevacizumab is a humanized monoclonal antibody (IgG1) targeting VEGF-A to inhibit angiogenesis, and is composed mainly of an Fab region that binds to the target and an Fc region that performs an effector function [49] . Fothurmore, ranibizumab is also a humanized monoclonal antibody fragment, but it only contains an Fab fragment, which can also inhibit VEGF-A and prevent the formation of new blood vessels [50] .…”
Section: Discussionmentioning
confidence: 99%
“…43 Besides, bevacizumab is a humanized monoclonal antibody (IgG1) targeting VEGF-A to inhibit angiogenesis, in addition, it is mainly composed of a fab region that binds to the target and an Fc region that performs an effector function. 44 What's more, ranibizumab is also a humanized monoclonal antibody fragment, but it only contains Fab fragment, which can also inhibit VEGF-A and prevent the formation of new blood vessels. 45 As one of the most commonly used anti-VEGF drugs, ranibizumab, and bevacizumab are commonly used to compare e cacy with each other, but they are currently considered to have the same e cacy in improving visual acuity in mCNV patients without statistical difference.…”
Section: Discussionmentioning
confidence: 99%
“…When VEGF is overproduced, conditions such as DME, aged-related macular degeneration, or DR can occur. The severity of vascular leakage in DME correlates with the level of VEGF produced and therefore anti-VEGF agents, such as ranibizumab (Lucentis, Genentech Inc., South San Francisco, CA, USA), bevacizumab (Avastin, Genentech Inc, South San Francisco, CA, USA), PRO-169 (anti-VEGF monoclonal antibody for intravitreal administration, Laboratorios Sophia, S.A. de C.V., Zapopan, Jalisco, Mexico), are used to inhibit it [ 9 12 ]. Nevertheless, it has been suggested that the use of anti-VEGF agents may result in systemic absorption, leading to further reduction in plasma VEGF activity, which turn produces accelerated hypertension, worsening proteinuria, glomerular disease, and possible chronic renal function decline [ 2 , 13 ].…”
Section: Introductionmentioning
confidence: 99%